A New Approach to Designing Advance Stress Release Boreholes to Mitigate Rockburst Hazards in Deep Boring-Machine-Constructed Tunnels - Zhenkun Xie; Shili Qiu; Shaojun Li; Yaxun Xiao; Minzong Zheng; Zhihao Kuang (Applied Sciences)
The use of tunnel boring machines (TBMs) in deep hard rock tunnels disrupts the original stress equilibrium of the rock mass, often resulting in the aggregation and release of a large amount of elastic strain energy, and even leading to rockburst. Under extremely high rockburst proneness conditions, advance stress release boreholes (ASRBs) deployed behind the TBM cutter head can be used to reduce stress concentration levels. However, there is a lack of scientific design methods for the parameters of the ASRB program for TBM tunnels, leading to poor stress release and difficulty in mitigating high-intensity rockburst hazards. This study proposes a parameter design method for ASRBs in the potential rockburst seismic source area of deeply buried hard rock TBM tunnels, including test scheme establishment methods, parameter selection methods, and parameter space relationship and evaluation index establishment methods. A deep tunnel in southwest China was used as an engineering case study to explore the effect of stress release and energy dissipation under different ASRB layout schemes. The results show that the sensitivity of the five important design parameters of ASRBs to the stress release effect is, in descending order, “aperture”, “inclination”, “included angle”, “spacing”, and “length”. A parameter control law for ASRBs is proposed, which confirms their effectiveness in preventing, controlling, and reducing rockburst disasters in deep hard rock TBM tunnels.